Galaxies in the act of quenching star formation. Issue 3 (28th April 2018) - Quai, Salvatore; Pozzetti, Lucia; Citro, Annalisa; Moresco, Michele; Cimatti, Andrea
ABSTRACT: Detecting galaxies when their star formation is being quenched is crucial to understand the mechanisms driving their evolution. We identify for the first time a sample of quenching galaxies selected just after the interruption of their star formation by exploiting the [$\rm{O\, \small {III}}$ ] λ5007/H α ratio and searching for galaxies with undetected [$\rm{O\, \small {III}}$ ]. Using a sample of ∼174000 star-forming galaxies extracted from the SDSS-DR8 at 0.04 ≤ z < 0.21, weidentify the ∼300 quenching galaxy best candidates with low [$\rm{O\, \small {III}}$ ]/H α, out of ∼26000 galaxies without [$\rm{O\, \small {III}}$ ] emission. They have masses between $\rm 10^{9.7}$ and $\rm 10^{10.8}\, M{_{{\odot }}}$, consistently with the corresponding growth of the quiescent population at these redshifts. Their main properties (i.e. star-formation rate, colours, and metallicities) are comparable to those of the star-forming population, coherently with the hypothesis of recent quenching, but preferably reside in higher-density environments. Most candidates have morphologies similar to star-forming galaxies, suggesting that no morphological transformation has occurred yet. From a survival analysis we find a low fraction of candidates (∼0.58 per cent of the star-forming population), leading to a short quenching time-scale of tQ  ∼ 50 Myr and an e -folding time for the quenching history of τ Q  ∼ 90 Myr, and their upper limits of tQ  < 0.76 Gyr and τ Q <1.5 Gyr, assuming as quenching galaxies 50 per cent of objects without [$\rm{O\, \small {III}}$ ] (${\sim }7.5\hbox{ per cent}$ ). Ourresults are compatible with a 'rapid' quenching scenario of satellites galaxies due to the final phase of strangulation or ram-pressure stripping. This approach represents a robust alternative to methods used so far to select quenched galaxies (e.g. colours, specific star-formation rate, or post-starburst spectra).